Influenza B Lineages Have More in Common Than Meets the Eye. Trivalent Influenza Vaccines Trigger Heterotypic Antibodies Against Both Influenza B Viruses - Sánchez-de Prada, Laura; Rojo-Rello, Silvia; Domínguez-Gil, Marta; Tamayo-Gómez, Eduardo; Ortiz de Lejarazu-Leonardo, Raúl; Eiros, José María; Sanz-Muñoz, Iván (Frontiers in Microbiology, 2021)
Influenza B is accountable for an important burden during flu epidemics, causing special impact in children and the elderly. Vaccination is the best approach to address influenza infections. However, one of the main problems of this virus is that two different lineages circulate together, Victoria and Yamagata; and trivalent vaccines, that only contain one of these lineages, are still in use. For that reason, if during an epidemic, the lineage not included in the vaccine predominates, a mismatch would occur, and the vaccine effectiveness will be very poor. In this work, we evaluated the cross-protection given by the trivalent Influenza vaccine and compared serological profiles based on age, sex, and the type of vaccine used. We performed a retrospective analysis of serum samples obtained before and after seasonal influenza vaccination during 20 seasons (1998-2018). The results showed that heterotypic reactivity between both influenza B lineages are common, but always lower than the homologous response. Age is a relevant factor for this cross-reactivity between both lineages, while the sex and the type of vaccine not. Vaccination with trivalent influenza vaccines elicits cross-reactive antibodies against both lineages, however, this response might not be enough to provide an appropriate serological protection in case of mismatch.